IgG4:IgG RNA ratio differentiates active disease from remission in granulomatosis with polyangiitis: a new disease activity marker? A cross-sectional and longitudinal study - Al-Soudi, A.; Doorenspleet, M. E.; Esveldt, R. E.; Burgemeister, L. T.; Hak, A. E.; van den Born, B. J. H.; Tas, S. W.; van Vollenhoven, R. F.; Klarenbeek, P. L.; de Vries, N. (Arthritis research & therapy, 2019)
An important limitation in granulomatosis with polyangiitis (GPA) is the lack of disease activity markers. Immunoglobulin G4-positive (IgG4 ) B cells and plasma cells are implicated in the pathogenesis of GPA. We hypothesized that the presence of these cells in peripheral blood could serve as disease activity parameter in GPA. We included 35 proteinase 3-antineutrophil cytoplasmic antibodies-positive patients with GPA in a cross-sectional study. Active disease was defined as Birmingham Vasculitis Activity Score (BVAS) ≥ 3 (n = 15), remission as BVAS of 0 (n = 17), and low disease activity (LDA) as BVAS of 1-2 and clinical remission (n = 3). Healthy subjects (n = 10), patients with systemic lupus erythematosus (n = 24), and patients with rheumatoid arthritis (n = 19) functioned as control subjects. An additional longitudinal study was performed in ten patients with GPA. Using a validated qPCR test, we measured the IgG4:IgG RNA ratio in all groups and compared the results with known biomarkers. The median qPCR score was higher in active GPA (21.4; IQR 12.1-29.6) than in remission/LDA (3.3; IQR 1.6-5.6) (Mann-Whitney U test, p < 0.0001) and outperformed other known disease activity parameters in detecting activity. A cutoff qPCR score of 11.2% differentiated active disease from remission/LDA accurately (AUC 0.993). The qPCR test correlated well with the BVAS (Spearman r = 0.77, p < 0.0001). In the longitudinal study, a decrease in BVAS correlated with qPCR score reduction (paired t test, p < 0.05). The IgG4:IgG RNA ratio in GPA accurately distinguishes active disease from remission and correlates well with disease activity in these single-center studies. If these results are confirmed in larger longitudinal studies, this test might help to steer treatment decisions in patients with GPA.